The Antimicrobial Photodynamic Therapy in the Treatment of Peri-Implantitis - Umberto Romeo; Gianna Maria Nardi; Fabrizio Libotte; Silvia Sabatini; Gaspare Palaia; Felice Roberto Grassi (Hindawi Limited, 2016)
Introduction. The aim of this study is to demonstrate the effectiveness of addition of the antimicrobial photodynamic therapy to the conventional approach in the treatment of peri-implantitis. Materials and Methods. Forty patients were randomly assigned to test or control groups. Patients were assessed at baseline and at six (T1), twelve (T2), and twenty-four (T3) weeks recording plaque index (PlI), probing pocket depth (PPD), and bleeding on probing (BOP); control group received conventional periodontal therapy, while test group received photodynamic therapy in addition to it. Result. Test group showed a 70% reduction in the plaque index values and a 60% reduction in PD values compared to the baseline. BOP and suppuration were not detectable. Control group showed a significative reduction in plaque index and PD. Discussion. Laser therapy has some advantages in comparison to traditional therapy, with faster and greater healing of the wound. Conclusion. Test group showed after 24 weeks a better value in terms of PPD, BOP, and PlI, with an average pocket depth value of 2 mm, if compared with control group (3 mm). Our results suggest that antimicrobial photodynamic therapy with diode laser and phenothiazine chloride represents a reliable adjunctive treatment to conventional therapy. Photodynamic therapy should, however, be considered a coadjuvant in the treatment of peri-implantitis associated with mechanical (scaling) and surgical (grafts) treatments.